Testosterone Replacement in Men with Treated and Untreated Prostate Cancer. Issue 3 (23rd September 2013) - Khera, Mohit
Abstract: Introduction: Historically, men with a history of prostate cancer have been deprived of testosterone because of the potential risk of prostate cancer progression and/or recurrence. However, we have lacked sound scientific evidence demonstrating that testosterone replacement therapy (TRT) actually does cause prostate cancer progression and/or recurrence in men with a history of prostate cancer. Our decision to withhold testosterone from these patients is based on several series of case reports and our current understanding of androgen deprivation therapy (ADT). Aim: To assess the safety of testosterone replacement therapy in men with treated and untreated prostate cancer. Methods: A Medline search was conducted from 1940 to 2013 using key words testosterone, prostate cancer, prostate specific antigen, and androgen. All manuscripts relevant to the use of testosterone in men with treated and untreated prostate cancer were reviewed and considered. Results: Recent data suggest that TRT may be safe in men with a history of prostate cancer, but clearly more studies are needed. Low‐serum testosterone levels have been associated with greater risk of prostate cancer and higher grade of disease. The rate of prostate cancer progression and recurrence in men treated for prostate cancer tends to be lower than in those men not being treated with TRT. There are now data to suggest that TRT may be protective against the development and recurrence of prostate cancer. The prostate saturation model allows us to understand these changes in prostate specific antigen in response to TRT and ADT. Conclusion: TRT may be safe in men with treated and untreated prostate cancer but further larger randomized placebo controlled studies are needed.Khera M. Testosterone replacement in men with treated and untreated prostate cancer. Sex Med Rev 2013;1:143–149.